McGraw-Hill's German student dictionary - Byrd, Erick P. frey50 (New York : McGraw-Hill, 2009)
For beginners, this dictionary provides the basic words you need, not the advanced terms you don't. It also includes subentries to explain shades of meaning and idiomatic expressions related to the principal entries; a collection of grammar tips and hints, including common mistakes to avoid; and helpful appendices of useful information such as common names in German, weights and measures, maps, numbers and more.
"Just the essential words beginners need to know"--Cover.
Keywords: German language -- English; English language -- German; English language; German language; Dictionaries